2012
DOI: 10.1007/s10924-012-0420-y
|View full text |Cite
|
Sign up to set email alerts
|

Use of Nutshells as Fillers in Polymer Composites

Abstract: Nutshells are agricultural waste products that can be procured at relatively low cost. In this work we examined the possibility of using these biodegradable materials as fillers in poly(lactic acid) and low density polyethylene. The nutshells were ground into powder, blended with the polymer, and then injection molded with final weight varying from 10 to 40 weight %. The mechanical and thermal properties of the composites were then studied. In general, the addition of fillers caused reductions in mechanical pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 76 publications
4
47
0
5
Order By: Relevance
“…Δ H m , Δ H m , represents melting enthalpy of the sample and melting enthalpy of 100% crystalline low density polyethylene (293 j g −1 ), respectively . W indicates the weight fraction of LDPE in the composites.…”
Section: Methodsmentioning
confidence: 99%
“…Δ H m , Δ H m , represents melting enthalpy of the sample and melting enthalpy of 100% crystalline low density polyethylene (293 j g −1 ), respectively . W indicates the weight fraction of LDPE in the composites.…”
Section: Methodsmentioning
confidence: 99%
“…Many semi-crystalline polymers show multiple melting peaks due to bimodal crystal distributions produced by annealing, reorganization and recrystallization, polymorphism and different molecular weight species [52]. This phenomenon is also found for neat PLA and PLA blends and composites in the literatures [3,7,8,9,18,23,25,27,31,33,38,39]. The WAXD spectra (Figure 7) indicate that only one crystalline modification was developed in the samples and the double melting peak seen in the DSC heating run may reflect the melting of crystalline regions of various sizes and perfection.…”
Section: Resultsmentioning
confidence: 85%
“…Some authors have reported that fillers added to thermoplastic matrices restrict the movement of the chains of the polymeric material (reducing ductility), thereby increasing the modulus of elasticity [7]. However, the biocomposites of the neat PLA mixed with organic fillers without coupling agents had shown a similar tendency in the mechanical parameters [13,14].…”
Section: Densitymentioning
confidence: 99%
“…Hence, it is desirable to use fillers of a natural origin that do not affect the biodegradability of the PLA matrix. The incorporation of natural fillers to the PLA and other polymer matrices has been reported by some authors [3,5,[13][14][15][16][17]. Some aspects, such as cost reduction, along with an improvement in the physical, chemical, mechanical, and thermal properties, are motivating the development of the 2 International Journal of Polymer Science biocomposites in order to reduce the use of synthetic plastics obtained from the oil.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation